STUDENTS’ PERCEPTIONS TOWARDS THE USE OF GOOGLE CLASSROOM FOR TEACHING ENGLISH TO GRADE X IN SMAN 1 AEK NATAS - Anggi Purwati Munthe; Indra Hartoyo (Universitas Negeri Medan, 2021)
This study was aimed to investigate the student’s perceptions towards the use of Google Classroom. The research was conducted at SMAN 1 Aek Natas. The research was descriptive qualitative research. The subject of this research was thirty-one students of SMAN 1 Aek Natas grade X have been using Google Classroom for teaching English. The results shows that Google Classroom is being helped for the students for study during this pandemic. Online learning can not completely replace conventional learning in the class but this system needs to be continuously developed for more effective learning.Keywords: Students' perceptions, Google Classroom, English teaching.